2004
DOI: 10.1159/000082334
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgeon Volume on Clinical and Economic Outcomes of Laparoscopic Cholecystectomy

Abstract: Background and Purpose: The volume-outcome effect has been well documented in both medical treatment and surgery. The relationship of volume-outcome utilization in laparoscopic cholecystectomy has not been studied. The aims of this study were to examine whether the operational volume of individual surgeons is associated with the clinical and economic outcomes of patients with gallbladder diseases undergoing laparoscopic cholecystectomy. Methods: A retrospective study was made of all patients who underwent elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
2
9
0
8
Order By: Relevance
“…Seventy‐five (20.4%) of 367 patients encountered postoperative complications in the CLC group. Nine (2.45%) patients suffered from biliary tract‐related complications, Grade IIIa, and one (0.45%) from incisional hernia, Grade IIIb, although most of them, 64 out of 75 patients (85%), experienced minor complications; Clavien‐Dindo classification Grade I, 50 patients; Grade II, 14 patients in this study with major complications including retained common bile duct (CBD) stone, bile duct stricture(injury), bile juice leakage, and subhepatic fluid collection as similar to previous reports with a range of 1.2∼3.6% [14–20]. For two decades, major complications of LC still cannot be avoided.…”
Section: Discussionsupporting
confidence: 89%
“…Seventy‐five (20.4%) of 367 patients encountered postoperative complications in the CLC group. Nine (2.45%) patients suffered from biliary tract‐related complications, Grade IIIa, and one (0.45%) from incisional hernia, Grade IIIb, although most of them, 64 out of 75 patients (85%), experienced minor complications; Clavien‐Dindo classification Grade I, 50 patients; Grade II, 14 patients in this study with major complications including retained common bile duct (CBD) stone, bile duct stricture(injury), bile juice leakage, and subhepatic fluid collection as similar to previous reports with a range of 1.2∼3.6% [14–20]. For two decades, major complications of LC still cannot be avoided.…”
Section: Discussionsupporting
confidence: 89%
“…Differences in national health conditions may explain the discrepancy. An earlier Taiwan study of cholecystectomy patients reported that percutaneous transhepatic gallbladder drainage may be a major cause of increased ALOS [20]. A longer preoperation hospital day may also increase ALOS.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the common bile duct is well known as a major contributor to cost and resource utilization, with immediate associated costs ranging from $13,612 to $30,000 and lifetime costs reported as high as $300,000 [21][22][23][24] . In addition, various patient, hospital, and surgeon factors -such as age, sex, presence of comorbidities, urgency of admission and surgery, length of stay (LOS), treatment in a regional or district hospital, hospital volume, and surgeon experience [25][26][27][28][29][30][31][32] -have been shown to affect cholecystectomy outcomes and associated overall resource use and costs.…”
Section: Case: the Cholecystectomy And Contributors To Resource Usementioning
confidence: 99%